Incidence and predictors of splanchnic vein thrombosis and mortality following hepatobiliary and pancreatic surgery - Duceppe E; Lauzon J; Galliger S; Zhang B; Solomon H; Serrano PE (Wiley, 2020)
BACKGROUND: Intraabdominal surgery is a known risk factor for splanchnic vein thrombosis (SVT). SVT incidence, management, and prognosis after hepatopancreatobiliary surgery are unknown. OBJECTIVES: To determine the incidence and prognosis of SVT following hepatopancreatobiliary surgery and describe current practices in anticoagulation for postoperative SVT. PATIENTS/METHODS: Multicenter retrospective cohort study of adults undergoing hepatopancreatobiliary surgery. Multivariable analyses for predictors of SVT, major bleeding, and 90-day mortality were performed. RESULTS: Of 1815 patients included, 89 (4.9%) had cirrhosis and 1532 (84.4%) had active cancer. The most frequent surgeries were pancreaticoduodenectomy (40.6%), open (30.7%), and laparoscopic (11.0%) liver resection. Sixty (3.3%) patients experienced SVT within 90 days of surgery. Among patients with SVT, 23.3% were symptomatic and 75.0% were treated with therapeutic anticoagulation. Planned duration of anticoagulation averaged 3 to 6 months. By multivariable analysis, SVT predictors were: operative time (adjusted odds ratio [aOR] per hour increase 1.32, 95% confidence interval [CI] 1.20-1.46), cirrhosis (aOR 3.22, 95% CI 1.28-8.10), and postoperative intraabdominal infection (aOR 2.99, 95% CI 1.72-5.19). Postoperative major bleeding occurred in 22.1% of patients and 4.0% died within 90 days. Predictors of postoperative mortality were age (aOR per 10-year increase 1.79, 95% CI 1.38-2.30), operative time (aOR 1.31 (1.17-1.45), cirrhosis (aOR 4.42, 95% CI 1.96-9.96), postoperative intraabdominal infection (aOR 2.66, 95% CI 1.55-4.57), postoperative major bleeding (aOR 4.12, 95% CI 2.36-7.30), and postoperative SVT (aOR 3.15, 95% CI 1.42-6.97). CONCLUSION: SVT occurred in 1 in 30 patients after hepatopancreatobiliary surgery and was associated with a 3-fold independent increase in 90-day mortality.
Keywords: anticoagulants; mortality; observational study; postoperative complications; surgery; venous thrombosis